Diagnostic Yield of Routine EEG with Video: A Retrospective Analysis of Its Clinical Utility in Adults at a Tertiary Care Center - Sachin, Sachin; Verma, Archana; Mishra, Ashutosh Kumar; Sachan, Divyata; Shadab, Md; Fatima, Syeda Shadma; Kumar, Alok (International Journal of Epilepsy, 2025)
Routine electroencephalography (EEG) with video (rVEEG) is a widely used, noninvasive neurodiagnostic tool that aids in the diagnosis and classification of epilepsy by detecting interictal epileptiform discharges. This study aimed to assess its diagnostic utility and identify key clinical correlates in adult patients at a tertiary care center in North India, where specific data on its yield in this resource-constrained context are valuable.We retrospectively analyzed routine EEGs with simultaneous video recording performed in adults aged ≥18 years. Clinical and demographic data—including seizure type, age at onset, etiology, antiepileptic drug use, seizure timing, and activation procedures—were extracted from EEG records and electronic medical records. EEGs were categorized as normal or abnormal, with abnormalities classified as epileptiform or nonepileptiform.Among 347 patients (mean age 41.6 ± 17.8 years), most were aged 18 to 30 (58.2%), with 41.4% experiencing seizure onset before the age of 18 years. Focal seizures were predominant (76.3%), especially focal impaired awareness seizures (52.7%). Etiology was unclear in 85.3% of cases. Neuroimaging data (computed tomography or magnetic resonance imaging) were available for 74 patients; 40 had normal findings, and 34 showed lesions. rVEEGs were commonly performed within 1 week of the last seizure (83%), often during sleep (57.3%). EEG abnormalities were present in 37.5%, primarily generalized spike-and-wave discharges (25.6%). Most patients were on monotherapy (86.2%). Video recording led to a revision or refinement of the initial clinical diagnosis in 7.5% (26) of patients. No significant clinical predictors of abnormal EEG findings were identified (p > 0.05).The diagnostic yield of rVEEG in this cohort was modest. Optimizing patient selection based on detailed clinical history may improve EEG utility in resource-constrained settings.
Keywords: routine EEG with video; epilepsy; diagnostic yield; seizures; resource-limited settings